Reproductive health knowledge and practices among students in public secondary schools in Ebonyi State, Nigeria - Nnebuife, Deborah Alegu; Elom, Nwamaka Agbe; Ilo, Cajetan Ikechukwu; Elom, Sampson Omena; Ojide, Rita Ngozika; Matthias-Ede, Uzoamaka Mercy; Orji, Scholarstica A.; Nwali, Chinwe Lynda (International Journal of Human Kinetics, Health and Education, 2023)
Reproductive health problems are a major public health problem among adolescents aged 10-19 years. In Nigeria, male and female adolescents suffer from sexually transmitted infections such as gonorrhea, syphilis, genital warts, candidiasis and trichomoniasis. This study determined reproductive health knowledge and practices among students in public secondary schools in Ebonyi State, Nigeria. The cross-sectional survey was adopted for the study. A sample of 500 students in public secondary school in Ebonyi State, Nigeria was enrolled for the study. The instrument used for data collection was researcher-designed questionnaire. Out of 500 copies of questionnaire administered; 496 representing 99.2% return rate, were used for analysis of data. Results showed that respondents had good (79.3%) knowledge concerning reproductive health but had low practice (2.13±0.68). Male and female students had average knowledge of reproductive health. Male and female students had average knowledge of reproductive health. However, female students dispositions to reproductive health practices were high while males were low based on their scores. The differences were significant in the knowledge of reproductive health based on gender (256.517, p=0.000) and practices (t-value=8.529, p=0.000). The study concluded that disparities in the level of knowledge and reproductive practices are still existing among the population studied especially the male ones. The study therefore, advocate for intensive reproductive health education programmes to students by secondary school teachers both in the classroom and during moral instruction.